Avaliação farmacológica neurocognitiva e de qualidade de vida de pacientes esquizofrênicos tratados com haloperidol e risperidona - Souza, Valéria Barreto Novais e (2003)
Introduction: Schizophrenia pharmacological therapy consists basically by two groups of antipsychotic drugs: typical and atypical. Response to pharmacological treatment with antipsychotics has been related to factors such drug dose and serum leveis. The newer antipsychotics treat positive and negative symptoms provoking fewer extrapyramidal side effects compared to the older antipsychotics. Atypical antipsychotics have been associated with improvement in cognition resulting in positive changes in social adjustment of schizophrenic patients. Therefore evaluations comparing action of antipsychotic groups in negative symptoms, cognition and social and occupational aspects in Brazil are important. Objectives: The present study aims to evaluate schizophrenic out-patients observing interrelations between pharmacotherapy, cognition and quality of life. The main objectives are: 1) To compare cognitive performance between patients treated with haloperidol and risperidone. 2) To observe if there is any correlation between used drug serum leveis, clinicai, social and occupational variables. 3) To compare social behavior between groups. Methods: The sample consisted of schizophrenic out - patients (n=84) treated with haloperidol (n=48) and risperidone (n=36) for at least six months at Messejana Mental Health Hospital. They were submitted to clinicai, cognitive, social and pharmacological evaluations. It was used the Brief Psychiatric Rating Scale (BPRS), Abnormal Involuntary Movement Scale (AIMS) and Body Mass Index (BMI) for clinicai evaluation. Similarities, Digit, Digit Symbol and Object Assembly tests were used for evaluation of cognitive functions. Social Behavior Scale was used to evaluate social adjustment. High Performance Liquid Chromatography (HPLC) was the method used to dose both antipsychotics in patienfs serums. Results: Haloperidol and risperidone showed efficacy in controlling schizophrenia symptoms, however haloperidol induced more extrapiramidal symptoms and greater need for anticholinergics. BMI were similar in both groups. The risperidone group showed better performance in tests that evaluate thinking process, concentration, short and working memory, psicomotor performance and visual organizational capability. Age, use of anticholinergic, high doses and antipsychotic politherapy showed to influence negatively in test performance. Both groups showed good social adjustment. The only difference was on weekly occupation where the risperidone group showed more engagement. Haloperidol high serum leveis exhibited an association with worse cognitive performance, while risperidone high serum leveis was correlated to behavior difficulties interfering in social relations. Conclusions: Haloperidol and risperidone showed similar efficacy, but the first provoked more extrapiramidal symptoms. The risperidone group showed a better performance in cognitive tests. Anticholinergic drugs interfered in memory. Use of more than one antipsychotic showed to worsened cognition. The risperidone group showed better occupational adjustment. Haloperidol high serum leveis were associated to worse cognitive performance while risperidone high serum leveis were related to behavior problems that make social relations difficult.